Diabetes Diagnostic Expert System using Website-Based Forward Chaining Method - Tiara Khumaira Putri; Mahda Laina Arnumukti; Khusnul Khatimah; Egidya Zalsabila; Sudianto Sudianto (Indonesian Journal of Data Science, IoT, Machine Learning and Informatics, 2023)
Diabetes is a chronic disease. The World Health Organization predicts that Indonesia's number of diabetic patients will continue to increase significantly to 16.7 million in 2045. As early prevention, early diagnosis is needed to anticipate more severe diabetes. This study aims to build an expert system for detecting diabetes using a web-based forward chaining method. The expert system is built by collecting indications from experts by collecting facts using the forward chaining method. Furthermore, judging by the unhealthy lifestyle of many people who consult with hospitals or health workers. From the results obtained, the system can work well based on knowledge from experts